2021
DOI: 10.1097/qad.0000000000002954
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of pregnancies in women with HIV over a 20-year period

Abstract: c , for the EuroSIDA Study GroupObjective: To evaluate time trends in pregnancies and pregnancy outcomes among women with HIV in Europe.Design: European multicentre prospective cohort study.Methods: EuroSIDA has collected annual cross-sectional audits of pregnancies between 1996 and 2015. Pregnancy data were extracted and described. Odds of pregnancy were modelled, adjusting for potential confounders using logistic regression with generalized estimating equations.Results: Of 5535 women aged 16 to <50 years, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
4
1
1
Order By: Relevance
“…Data on behavioural factors (diet, exercise, level of alcohol consumption) were not collected in EuroSIDA. Data on pregnancies [37], thyroid disease, substance use, depression and psychiatric illness including use of antidepressants and antipsychotics were collected inconsistently over time and between clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Data on behavioural factors (diet, exercise, level of alcohol consumption) were not collected in EuroSIDA. Data on pregnancies [37], thyroid disease, substance use, depression and psychiatric illness including use of antidepressants and antipsychotics were collected inconsistently over time and between clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, Haddad et al 6 , in a study conducted in 9 U.S. centers, reported a non-significant increase in pregnancy incidence in WLWHA and a significant increase in live births (from 2.85 to 7.27/100 person-years) in the periods 1994-1997 to 2006-2012, with similar values in WLWHA and in women not living with HIV/AIDS (WNLWHA) in more recent periods. Studies in Canada 7 and Europe 22 also report an increased number of pregnancies in WLWHA after the years 2000-2002. One study in Burkina-Faso 20 showed an increase in pregnancy incidence in women using ART for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although over 80% of the nearly 50,000 women newly diagnosed with HIV in Europe in 2018 were fertile-aged [ 8 ], little is known about the rates and risk factors for induced abortions among women living with HIV (WLWH). Most data come from limited questionnaire studies with varying response rates [ 9 11 ]. In questionnaire studies on the general population, induced abortions have been significantly underreported [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%